2019
DOI: 10.35940/ijitee.a4830.119119
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Defining the Notion of Social Entrepreneurship

Abstract: The paper presents the results of an interdisciplinary comparative analysis of modern research practices concerning social entrepreneurship in Russian and foreign traditions in order to establish the specifics of defining the notion of social entrepreneurship in interdisciplinary discourse. The analytical basis of the study comprised the fundamental provisions and concepts of open innovation and human capital, the theory of public goods, the theoretical provisions concerning the structure and substance of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…La construcción final del instrumento está alineada a las características contextuales de interés para los investigadores, es decir, en procesos formativos universitarios en donde el fomento del emprendimiento social responde a una de las necesidades educativas elementales en la formación profesional de los jóvenes. El desarrollo de este obedeció a una revisión de literatura respecto a las concepciones de emprendimiento social (Alegre et al, 2017; Austin et al, 2006; Granados et al, 2011) y el perfil de las competencias que requiere el emprendedor social (Gandhi and Raina, 2018;Light, 2009;Saxena, 2019;Shapovalov et al, 2019;Thompson et al, 2000). Tomamos como base la operacionalización de Lackéus (2014), para iniciar a identificar las competencias fundamentales en emprendimiento, agregando los rasgos característicos del emprendimiento social manifestados por Miller et al (2012), Orhei et al (2015) y Sáenz-Bilbao & López-Vélez (2015); además de la consulta de instrumentos similares (Capella-Peris et al, 2016Portuguez et al, 2018;Velasco Martínez et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La construcción final del instrumento está alineada a las características contextuales de interés para los investigadores, es decir, en procesos formativos universitarios en donde el fomento del emprendimiento social responde a una de las necesidades educativas elementales en la formación profesional de los jóvenes. El desarrollo de este obedeció a una revisión de literatura respecto a las concepciones de emprendimiento social (Alegre et al, 2017; Austin et al, 2006; Granados et al, 2011) y el perfil de las competencias que requiere el emprendedor social (Gandhi and Raina, 2018;Light, 2009;Saxena, 2019;Shapovalov et al, 2019;Thompson et al, 2000). Tomamos como base la operacionalización de Lackéus (2014), para iniciar a identificar las competencias fundamentales en emprendimiento, agregando los rasgos característicos del emprendimiento social manifestados por Miller et al (2012), Orhei et al (2015) y Sáenz-Bilbao & López-Vélez (2015); además de la consulta de instrumentos similares (Capella-Peris et al, 2016Portuguez et al, 2018;Velasco Martínez et al, 2019).…”
Section: Discussionunclassified
“…Así como se relaciona el concepto de emprendimiento comercial con el emprendimiento social, el perfil del emprendedor social coincide con el perfil del emprendedor que busca la generación de utilidades en cierto aspecto. Algunos autores indican que el emprendedor social muestra un comportamiento proactivo orientado a ser un agente de cambio, posee la habilidad de identificar, crear y explotar oportunidades, se diferencia del emprendedor tradicional, en el sentido que el social genera un bien social para aquellas personas menos favorecidas dentro la sociedad (Shapovalov et al, 2019). Gandhi & Raina (2018: 6) afirman que los emprendedores sociales suelen caracterizarse por perseguir "ideas brillantes y contra todo pronóstico lograron crear nuevos productos y servicios que mejoraron dramáticamente las vidas de las personas a su alrededor"; pero lo que se considera fundamental es el reconocimiento de la oportunidad (Gandhi and Raina, 2018).…”
Section: Competencia De Emprendimiento Socialunclassified
“…First, the results show those competencies that are best perceived by the sample (Table 3), with the subcompetency related to personal values standing out. Indicators such as communication, knowledge of others, motivation, perseverance, and persuasion are undoubtedly fundamental elements of the social entrepreneur profile (Shapovalov et al 2019) (Gandhi and Raina 2018). However, these indicators can be considered generic since, by themselves, they do not contribute concrete tools to materialize ideas, as could indicators such as financing and administration, value generation, the management of limited resources, or the valuation of results and impact, which were indicators that, notably, had the lowest averages.…”
Section: Discussionmentioning
confidence: 99%
“…This notion seems to focus on the commitment and social responsibility of the entrepreneur above all things; however, at the end of the day, social entrepreneurship must involve sustainable projects, which implies good management of human, economic, and even temporal resources (Alvarez de Mon et al 2021). Although authors such as Shapovalov et al (2019) raise the importance of the entrepreneurs' social vision as a distinctive feature, they consider that one cannot lose sight of the need to have sufficient skills to identify, create, and develop opportunities, aspects that are shared with other, more traditional entrepreneurs. Gandhi and Raina (2018) point out that social entrepreneurs are characterized by their motivation to solve social problems, but that, regardless of this, they require having skills and knowledge about the economic reality that is necessary for any entrepreneurial proposal, such as motivation, effective communication, the search for financing, personal relationships, and even the ability to take risks in uncertain environments.…”
Section: Profile Of the Social Entrepreneurmentioning
confidence: 99%
“…Gandhi and Raina (2018) state that social entrepreneurs pursue brilliant ideas to create products and services that improve people's lives. Shapovalov et al (2019) agree, pointing out that the difference between the traditional and the social entrepreneur is the generation of social good for the less-favored. This is also in line with Sun and Cai (2013), who found that the social entrepreneur has a differentiating axis of social value.…”
Section: Multidisciplinarity In Social Entrepreneurship Competencementioning
confidence: 99%